PRIMARY AND SECONDARY PREVENTION OF IRON DEFICIENCY AT THE PRESENT STAGE - Kudratova Z.E.-PhD; Sirojeddinova S.F; Tursunova M.E (Western European Studies, 2024)
The problem of iron deficiency is primarily a nutritional problem, so the primary prevention of iron deficiency is an adequate, balanced nutrition of a person at any age. The daily iron requirement for an adult is about 1-2 mg, for a child - 0.5-1.2 mg. A normal diet provides an intake of 5 to 15 mg of elemental iron per day. Only 10-15% of dietary iron is absorbed in the GI tract (duodenum and upper jejunum) [3,4].
Keywords: iron; heme iron; hepcidin; body weight